The Right to Test the Constitutional Court in the Position as a Negative Legislator According to the 1945 NRI Constitution - Laritmas, Silfianus; Rosidi, Ahmad (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
The Constitutional Court, in accordance with Article 24C paragraph (1) and paragraph (2), has the authority to test laws against the 1945 Constitution of the Republic of Indonesia, to decide on disputes over the authority of state institutions whose authority is granted by the Constitution, this authority, There are several Constitutional Court decisions that are pros and cons, both related to the right to material review and the right to formal review. In the Constitutional Court decision Number 112/PUU-XX/2022, whose ruling extended the term of office of the Corruption Eradication Commission and finally the Constitutional Court Decision No. 90/PUU-XXI/2023 Regarding the Age Requirements for Presidential and Vice-Presidential Candidates. making the Constitutional Court no longer trustworthy as a judicial institution that acts as a Negative Legislator but has acted as a Positive Legislator. Regulations regarding changes to the Law are the authority of the Legislative and Executive, but now the role of the Constitutional Court regarding the formal and material testing of laws and regulations has played a role as a Positive Legislator whose authority is to create new legal regulations with its Decisions which are final and binding. The behavior of the Constitutional Court's Decision by using its authority as a Positive Legislator is no longer guided by the authority it has.